Development of a Scale to Measure Trust in Public Health Authorities: Prevalence of Trust and Association with Vaccination. Issue 4 (3rd April 2021) - Holroyd, Taylor A.; Limaye, Rupali J.; Gerber, Jennifer E.; Rimal, Rajiv N.; Musci, Rashelle J.; Brewer, Janesse; Sutherland, Andrea; Blunt, Madeleine; Geller, Gail; Salmon, Daniel A.
Abstract : Infectious disease outbreaks highlight the importance of trust in public health authorities to avoid fear and improve adherence to recommendations. There is currently no established and validated measure for trust in public health authorities. We aimed to develop and validate an instrument that measures trust in public health authorities and to assess the association between trust in public health authorities and vaccine attitudes. We developed 20 items to measure trust in public health authorities. After implementing a survey in January 2020, we investigated relationships between the items, reduced the number of items, and identified latent constructs of the scale. We assessed variability in trust and how trust was associated with vaccine attitudes, beliefs, and self-reported vaccine acceptance. The pool was reduced to a 14-item trust in public health authorities scale and we found that this trust model was strongly associated with acceptance of vaccines. Our scale can be used to examine the relationship between trust in public health authorities and adherence to public health recommendations. The measure needs to be validated in other settings to determine whether they are associated with other areas where the public question public health authority recommendations.